Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.32433/eje.421904
|View full text |Cite
|
Sign up to set email alerts
|

Lise Öğrencilerinin Yaşam Doyumu Düzeylerinin Çeşitli Değişkenler Açısından İncelenmesi

Abstract: The high school years that correspond to the period when the symptoms of adolescence are most intense are also a time when important decisions are made. On one hand adapting to the physical emotional and intellectual developments, on the other hand deciding on the choice of the profession and furthermore being in a fight with the whole world, is making the period even more challenging Satisfaction from life in these stormy years can become more difficult than ever. The aim of this research is to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…In studies examining the life satisfaction of secondary school students according to some variables, it was determined that being an only child or having more than one sibling did not affect life satisfaction. In some studies, examining the life satisfaction of secondary school students according to various variables, it was determined that being an only child or having more than one sibling did not affect life satisfaction, similar to the results of the research Civitci, 2009;Yazici-Celebi & Celebi, 2018). Studies have shown that the number of siblings does not affect resilience during the COVID-19 process , however, students with more siblings are more successful in coping with uncertainty and have higher tolerance for uncertainty (Ersoz, Ersoz & Konuskan, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In studies examining the life satisfaction of secondary school students according to some variables, it was determined that being an only child or having more than one sibling did not affect life satisfaction. In some studies, examining the life satisfaction of secondary school students according to various variables, it was determined that being an only child or having more than one sibling did not affect life satisfaction, similar to the results of the research Civitci, 2009;Yazici-Celebi & Celebi, 2018). Studies have shown that the number of siblings does not affect resilience during the COVID-19 process , however, students with more siblings are more successful in coping with uncertainty and have higher tolerance for uncertainty (Ersoz, Ersoz & Konuskan, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 53%
“…Bu sonuç açisindan bakildiğinda kardeş sayisina göre öğrencilerin yaşam doyumlari ve COVID-19 korkularinin benzer olduğu, öğrencilerin kardeş sayisinin yaşam doyumu ve COVID-19 korkusu üzerinde etkili bir değişken olmadiği söylenebilir. Ortaokul öğrencilerinin yaşam doyumlarinin çeşitli değişkenlere göre incelendiği bazi araştirmalarda, araştirma sonucuna benzer şekilde, tek çocuk veya birden çok kardeşi olmanin yaşam doyumunu etkilemediği belirlenmiştir Çivitçi, 2009;Yazici-Çelebi ve Çelebi, 2018). Yapilan araştirmalarda kardeş sayisinin COVID-19 sürecinde psikolojik sağlamliği etkilemediği ; bununla birlikte kardeş sayisi fazla olan öğrencilerin belirsizlikle baş etmede daha başarili olduklari ve belirsizliğe tahammüllerinin yüksek olduğu belirlenmiştir (Ersöz, Ersöz ve Konuşkan, 2016).…”
Section: Sonuç Ve Tartışmaunclassified